Morphological diversity in the honeyeater hyolingual apparatus and its relationship with nectarivory - Amanda E. Hewes; Cassandra Fieldson; Maude W. Baldwin; William A. Buttemer; Alejandro Rico-Guevara (PLoS ONE, 2025)
Honeyeaters (Aves, Meliphagidae) are a speciose clade of nectarivorous birds, and there is immense diversity in the degree to which different species within the family rely on nectar. Honeyeater tongues are commonly described as similar to a paintbrush, with this morphology being interpreted as an adaptation for increasing nectar extraction efficiency. However, there has been limited work documenting the degree of interspecific diversity in tongue morphology across the family or the extent to which such diversity correlates with dependance on nectar. This information is also lacking for the hyoid bones, the structures responsible for moving the tongue in and out of the mouth. We aimed to fill this knowledge gap by examining honeyeater tongues and hyoids from across the family. We found that there are six distinct tongue types across the Meliphagidae, and that certain genera such as Acanthorhynchus and Phylidonyris have a unique tongue morphologies. Using phylogenetic generalized least square regressions, we found that tongue length (not size corrected) and the proportion of tongue that is bristled were both positively correlated to degree of nectarivory, while tongue length (relative to bill length), tongue depth (relative to bill depth) and tongue width (relative to bill width) were not correlated to nectarivory. Finally, we found no correlation between hyoid length (relative to bill length) and nectarivory, suggesting that the capacity for further tongue protrusion is unrelated to nectar dependence in honeyeaters. Similar studies should be conducted across other groups of avian nectarivores to expand our understanding of dietary ecomorphology beyond bill shape, which has been the focus of the majority of research on food handling adaptations in birds thus far.